Shining light on an unspeakable crime: Necrophilia and the need for legal reform - Tippett, Anna (Current issues in criminal justice, 2024)
This article explores the current legal frameworks surrounding necrophilia in the United Kingdom. More specifically, it draws upon Aggrawal's [(2009). "A new classification of necrophilia". 'Journal of Forensic and Legal Medicine, 16'(6), 316-320] typologies of necrophilia, arguing that a multifaceted definition of necrophilia is required in order to properly legislate against it. The recent case of David Fuller is incorporated into discussions, and efforts towards legal reform are examined accordingly. The article makes recommendations of how future research can progress discussions in this acutely under-researched area of criminology and law.